Brain function in children with untreated epilepsy: Relationship to biomarkers of brain damage - Hamed, Sherifa A.; Eltayeb, Azza A.; Mohamad, Hanan O.; Moussa, Ehab M.M. (Journal of Pediatric Epilepsy, 2013)
Many studies have reported cognitive and behavioral abnormalities with recurrent seizures in adults. Similar evidence from the pediatric population is scarce and controversial. We aimed to investigate the effect of recurrent seizures on the developing brain. Included were 42 children with epilepsy (mean age 14.1 ± 1.72 yr) and 30 healthy children for comparison. Patients had recurrent untreated epilepsy (generalized or focal). Negative attitudes and misconceptions about epilepsy are common in developing countries, often resulting in neglect of medical services and treatment. Epilepsy is greatly misunderstood by the public, and is attributed to spiritual causes such as the devil or mistaken as odd behavior or daydreaming. Another misconception is that medications will harm the child. Intelligence quotient (IQ) and cognition were examined using Wechsler Intelligence Scale for Children and Stanford Binet Subsets Test version 4 (SBST4). Serum levels of neuron-specific enolase (NSE) and S100ß proteins, sensitive markers of neuronal and glial cell damage were measured. Compared to controls, patients had lower mean score of full scale IQ on the Wechsler Intelligence Scale for Children (P = 0.045), particularly performance IQ scores (P < 0.01), and comprehension, pattern analysis, quantitation, bead memory and memory for sentences of SBST4 (P = 0.045; P = 0.013, P = 0.007, P = 0.002; P = 0.035), but not for NSE or S100ß. Severe epileptogenic (EEG) records were observed in children with lower IQ. Serum concentrations of NSE and S100ß were lower in children with higher seizure frequency but did not reach significance compared to controls. Significant correlation was observed between full scale IQ and duration of illness (r = −0.430, P = 0.035), number of seizures (r = −0.580, P = 0.005) and severity of electroencephalography changes (r = −0.450, P = 0.052), but not with S100ß or NSE levels. Lower intelligence and poor cognitive performance were common with recurrent childhood epilepsy. Functional brain abnormalities without structural brain injury may likely be the cause. It seems that serum levels of NSE and S100ß are not sensitive markers for structural or minimal brain damage in children with untreated epilepsy. Thus, early recognition and optimal seizure control is necessary to prevent the subsequent damaging effects on the brain due to prolonged and recurrent seizures and subclinical epileptiform activity. Looking for additional, more specific markers of brain injury is necessary, elevated serum levels of NSE and S100ß were not detected.
Keywords: Children; idiopathic epilepsy; intelligence; cognition; S100ß protein; neuron-specific enolase